Pengaruh Penggunaan Aplikasi Hafalan Al-Qur’an pada Android terhadap Kemampuan Menghafal Al-Qur’an Siswa - Ikhsan, Ilian; Hayati, Zuqriva; M, Iswantir (FENOMENA, 2024)
The tradition of memorising the Koran has become a necessity in Islamic boarding schools, so teachers have made many innovations to make memorising the Koran enjoyable. Therefore, this research aims to see the differences in student learning outcomes before and after using the Koran memorisation application and the influence of the Koran memorisation application on students' memorisation abilities. The subjects of this research were class VII students at the Al-Irsyad Bulaan Kamba Islamic Boarding School, Agam Regency. Sampling used a purposive sampling technique. This research is a pre-experimental research using a one-group pretest-posttest design. The instrument that will be used in this research is a test. The data analysis technique used is the t-test, which uses the Paired Sample Test to calculate the N-Gain value. As for the Paired Sample Test calculation results on the overall student data, a significance value (Sig.) was obtained of 0.000, which means less/small than 0.05, and the N-Gain value was received with a score of 0.3656 in the medium category. This research showed that using the Koran memorisation application on Android improved students' ability to memorise the Koran.